Does loss of CD44, low E-Cadherin and high Ki-67 expression in equine malignant melanoma have a relationship with biological behavior? - Chaves Jorge, Alice [UNESP]; De Araújo Viana, Daniel; Regina Zapaterini, Joyce [UNESP]; Mauricio Montoya-Flórez, Luis; Sousa Rocha, Noeme [UNESP] (Universidad Nacional Mayor de San Marcos, Vicerectorado de Investigacion, 2024)
Equine melanoma affects all breeds and although 90% of melanocytic tumors in the species are benign, 66% of them progress to malignant forms and can metastasize, which translates into great economic losses for owners. For this, the investigation of prognostic factors and establishing their relationship with histopathological criteria is essential. The current work aimed to relate the expression of CD44, E-cadherin, and Ki67 with histopathological and cytological findings in equine melanomas, to identify a possible relationship between the anatomo-clinical expression and the biological behavior. Fifteen cases of melanoma in horses were selected, confirmed by cytopathological and/or histopathological exams (biopsy) taken from the files of the pathology laboratory of Universidade Estadual Paulista «Júlio de Mesquita Filho», Brazil. The samples were analyzed according to the presence of atypical cytological criteria and following the «Breslow» micrometric criteria. Subsequently, the samples were submitted to the immunohistochemical technique for S-100, CD44, Ki67, and E-cadherin (ECAD) markers. Descriptive statistics and non-parametric tests with significance p<0.05 were used for data analysis. In cytology, all samples showed a high degree of malignancy criteria, and all analyzed tumors were infiltrative (N3/TIII). CD44 expression was negative in all samples, the positivity rates for S-100, Ki67, and E-cadherin were 52.5, 50.43 and 10% respectively. It is suggested that the use of CD44, ECAD, and Ki67 together with cytopathological and histopathological analyses including the application of the «Breslow» criteria should be performed to identify equine melanomas with highest degree of aggressiveness and better establish the prognosis in this type of tumor.
¿la pérdida de CD44, baja expresión de E cadherina y alta expresión de Ki-67 en melanoma maligno equino tiene relación con su comportamiento biológico?
Keywords: Breslow; immunohistochemistry; melanoma; tumor